If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-3-x+2=14
We move all terms to the left:
6x-3-x+2-(14)=0
We add all the numbers together, and all the variables
5x-15=0
We move all terms containing x to the left, all other terms to the right
5x=15
x=15/5
x=3
| 10n+9=-111 | | 5-c8=43 | | 10=-7-f | | 2n+3=16-3n | | (3x-44)+4x+x=180 | | 3(x+2)-7+(2x=14) | | 9=b-10 | | 8y+2y+4y-2=5y | | X-12x+12=4-15x+9 | | y2+2y–2=0 | | -3/4d=15 | | 3x-4=3x+14 | | 3x-7+6x=38 | | -1/3(6n-9)+4(n+2)=0 | | 25=x/2-10 | | 12q-3q=3 | | 19.00+4.50x=10.00+5.75x | | 0.2=x/80+x | | 20y-14y=12 | | 21/3x-7/12=2x-3/2 | | 39−43+x=-46 | | 3x-5=4x-35 | | 17.5+q+R=32.5 | | 9x−1∘=6x+58∘=87∘ | | -22+28−x=-30 | | -15=b-8 | | a^+a-12=0 | | |x-10|+5=24 | | 9(4b–1)=2(9b+3) | | -4=5(b-2) | | Y-2=(x-5) | | (3h+4=) |